The Effectiveness of the Think-Pair-Project-Share (TP2S) Model in Facilitating Self Directedness of Prospective Science Teachers - Sajidan, Sajidan; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy; Saputri, Dwi Yuniasih; Roslan, Roslinawati Mohd; Halim, Lilia (Jurnal Pendidikan IPA Indonesia, 2024)
Self-directedness is a crucial skill for prospective science teachers, and the Think-Pair-Project-Share (TP2S) model has shown promise in fostering collaboration and critical thinking. This aim study to investigates the effectiveness of TP2S in promoting self-directed learning among these future educators. This research aims to determine the effectiveness of the think-pair-project-share (TP2S) learning model in facilitating the self-directedness of prospective science teachers. This quantitative research uses a nonequivalent control group design. The population in this study were second semester students, while the research sample consisted of 72 students. The self-directedness data collection technique uses an instrument in the form of a scale. Based on the results of the paired sample T test, it can be seen that both experimental classes obtained a Sig value. (2-tailed) 0.000. It can be concluded that the paired sample T test value in the experimental class is 0.000